Active power control from wind farms for damping very low-frequency oscillations - Duggan, Connor; Liu, Xueqin Amy; Best, Robert; Brogan, Paul; Morrow, John (Frontiers in Energy Research, 2022)
Timely remote activation of frequency response, provided by converter-based generation, can improve the damping of very low-frequency (VLF) oscillations. The research presented is based on both power system models and actual data from phasor measurement units (PMU) on the Irish power system. The performance of active power control (APC) is investigated, and variations in wind speed, droop, time lag and resource capacity demonstrate their effectiveness at damping wide-spectrum VLF modes. PMU data that captures the activation and deactivation of APC at wind farms is presented and analyzed; it demonstrates how APC control effectively dampens VLF modes on the Irish system. These observations are supported by sensitivity analysis carried out a power system model in DIgSILENT PowerFactory. These results demonstrate the improvement in VLF mode stability that APC can provide at wind generation. It is demonstrated that minimal amounts of generation curtailment and modest droop settings are sufficient to see substantial VLF mode damping.